Officiële Belgische Stripcatalogus deel 2. - Dewilde, Danny (Gent : 9de Kunst Grafiek Galerij, 1998)
Aragones, Sergio ; Armand, Jacques ; Attanasio, Dino ; Bailly, Pierre ; Basset, Brian ; Beker, Leo ; Beniest, Andre ; Berck (Berckmans, Arthur) ; Bercovici, Philippe ; Bergese, Francis ; Berthet, Philippe ; Bertrand, Francis ; Binsfeld ; Blesteau, Albert ; Bodart, Denis ; Bosmans, Serge (Bosse) ; Boucq, François ; Bourgeon, François ; Broca, Nicolaas ; Camille, Roger ( Kiko ) ; Caracostea-Balan, Pascal (Carabal ) ; Carpentier, Louis-Michel ; De Carpentrie, Daniel ; Chappuis, Philippe ( Zep ) ; Cicuendez, Juan Manuel ; Colin, Antoinette ; Colman, Stephane ; Conrad, Didier ; Cosendai, Bernard ( Cosey ) ; Cossu, Antonio ; Counhaye, Guy ; Coutelis, Alexandre-Nicolas ; Crombeecke, Luc ; Darasse, Christian ; David, Dominique ; Degotte, Charles ; Degroide, Marc ( Michetz ) ; Deliege, Paul ( Pol ) ; Denauw, Renaud ; Denis, Jean-Claude ; Denis, Marcel ; Desmesmaeker, Jean ( Jidéhem ) ; Desorgher, Daniel ; Dethorey, Jean-Paul ; Devos, Jacques ; Dineur, Fernand ; Dodier, Alain ; Drappier, Franz ; Dufosse, Bernard ; Dumont, Bernard ( Bédu ) ; Dupuy, Philippe ; Ernst, Serge ; Fernan, J.L. ; Foerster, Philippe ; Follet, René ; Forton, Gerald ; Fournier, Jean-Claude ; Fournier, Pierre ( Makyo ) ; Francq, Philippe ; Franquin, André ; Funcken, Fred ; Gabrion, Pierre-Yves ; Gall, Frank Le ; Garton, Jean ; Gazzotti, Bruno ; Geerts, André ; Geurts, Jean-Richart ( Janry ) ; Gianolla, F. ; Gibrat, Jean-Pierre ; De Gieter, Lucien ; Gillain, Joseph ; Gillon, Paul ; Giraud, Jean ; Goelen, Werner (Griffo) ; Goossens, Roland ( Gos ) ; Goossens, Walter ( Walt ) ; Graton, Jean ; Guibert, Emmanuel ; Hardy, Marc ; Harman, Fred ; Hausman, René ; Hiettre, Jean-Luc ; Hislaire, Bernard ; Hope ; Hubinon, Vicotr ; Huppen, Herman ( Hermann ) ; De Jager, Gerrit ; Jannin, Frederic ; etc.
Biog. per kunstenaar
boek